Pengaruh Digital Marketing Terhadap Minat Beli Konsumen Pada Market Place Shopee Di Kecamatan Tidore - Ruray, Titiek Arafiani (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to examine the effect of digital marketing on consumer buying interest at the shopee market place in Tidore District. Digital marketing is a marketing strategy that is that is carried out onlien using various digital media platforms, such as websites,social media,e-mail,and market places. One of the popular market places.one of the popular market places in Indonesia is Shoppe. The study uses a quantitative approach, by collecting data from respondents who are active shoppe users in Tidore Ditrict. The sample used in this study amounted to 40 respondents and used a non-probability sampling technique. The data analysic used was correlation analysis and simple linear regression analysis using SPSS version 20 software.The results of the data analysis showed that there was a positive influence between digital marketing and consumer purchasing power of 3.45%.